Effect of 12‐week dulaglutide therapy in Japanese patients with biopsy‐proven non‐alcoholic fatty liver disease and type 2 diabetes mellitus. Issue 11 (5th December 2016) - Seko, Yuya; Sumida, Yoshio; Tanaka, Saiyu; Mori, Kojiroh; Taketani, Hiroyoshi; Ishiba, Hiroshi; Hara, Tasuku; Okajima, Akira; Umemura, Atsushi; Nishikawa, Taichiro; Yamaguchi, Kanji; Moriguchi, Michihisa; et al.
Abstract : Aims: No pharmacological therapies have been established for non‐alcoholic fatty liver disease (NAFLD) with type 2 diabetes mellitus (T2DM). The aim of this retrospective study is to evaluate the efficacy and safety of dulaglutide, a novel glucagon‐like peptidase‐1 receptor agonist, in Japanese NAFLD patients with T2DM. Methods: Fifteen biopsy‐proven NAFLD patients with T2DM refractory to diet intervention who received once weekly dulaglutide 0.75 mg for 12 weeks were retrospectively enrolled after exclusion of two patients by 12 weeks. In five patients, transient elastography and body composition were also evaluated before and after the treatment. Results: Not only body weight and hemoglobin A1c but also transaminase activities were significantly decreased after the 12‐week therapy with dulaglutide. Total body fat mass and liver stiffness measurement also decreased after the treatment. Conclusion: Dulaglutide, a new glucagon‐like peptidase‐1 receptor agonist, could be a novel promising agent for the treatment for NAFLD patients with T2DM due to its efficacy in body weight reduction, the nature of weekly injection, and patient preference. Prospective randomized controlled trials are warranted to confirm this impact of dulaglutide on NAFLD with T2DM.